The phenotypic spectrum of SCN8A encephalopathy. (3rd February 2015) - Larsen, Jan; Carvill, Gemma L.; Gardella, Elena; Kluger, Gerhard; Schmiedel, Gudrun; Barisic, Nina; Depienne, Christel; Brilstra, Eva; Mang, Yuan; Nielsen, Jens Erik Klint; Kirkpatrick, Martin; Goudie, David; et al.
Abstract : Objective: SCN8A encodes the sodium channel voltage-gated α8-subunit (Nav 1.6). SCN8A mutations have recently been associated with epilepsy and neurodevelopmental disorders. We aimed to delineate the phenotype associated with SCN8A mutations. Methods: We used high-throughput sequence analysis of the SCN8A gene in 683 patients with a range of epileptic encephalopathies. In addition, we ascertained cases with SCN8A mutations from other centers. A detailed clinical history was obtained together with a review of EEG and imaging data. Results: Seventeen patients with de novo heterozygous mutations of SCN8A were studied. Seizure onset occurred at a mean age of 5 months (range: 1 day to 18 months); in general, seizures were not triggered by fever. Fifteen of 17 patients had multiple seizure types including focal, tonic, clonic, myoclonic and absence seizures, and epileptic spasms; seizures were refractory to antiepileptic therapy. Development was normal in 12 patients and slowed after seizure onset, often with regression; 5 patients had delayed development from birth. All patients developed intellectual disability, ranging from mild to severe. Motor manifestations were prominent including hypotonia, dystonia, hyperreflexia, and ataxia. EEG findings comprised moderate to severe background slowing with focal or multifocal epileptiform discharges. Conclusion: SCN8A encephalopathy presents in infancy with multiple seizure types including focal seizures and spasms in some cases. Outcome is often poor and includes hypotonia and movement disorders. The majority of mutations arise de novo, although we observed a single case of somatic mosaicism in an unaffected parent.